The Experience of Using «Virtual Petrolab» – Virtual Petrophysical laboratory for Mobile Devices in the Educational Process - E. V. Shelyago; N. D. Shelyago (Высшее образование в России)
The paper highlights the experience in the development and implementation of the “Virtual PetroLab” – virtual petrophysical laboratory for mobile devices (smartphones, tablets) in the educational process. The application was created to help the university professors to deliver the course “Oil formation physics”. The program “Virtual PetroLab” simulates functions of various petrophysical equipment in the lab, possesses built-in methodological instructions on performing laboratory works. The mathematical model of the application allows the student to conduct measuring tasks, make, accumulate and correct his own errors. The paper describes the principles of application design and organization of the educational process with its use. Using of mobile devices as a main platform for a virtual laboratory allowed the maximum involvement of the student audience in the educational process, improved the learning quality during workshops, received positive feedback from the students. The conclusions about high efficiency of using the virtual laboratories for mobile devices when teaching technical discipline are drawn.